Dinâmica de fósforo e eficiência de superfosfato triplo associado a biocarvões - Silva, Ronaldo Willian da (2021)
The accentuated degree of weathering dominance of Brazilian soils promotes characteristics such as low nutrient availability and high phosphorus (P) sorption capacity. Under these conditions, the soil acts as a P sink, competing for nutrient with the plants. The phosphate fertilization efficiency is low and there is a need to apply amounts of phosphate fertilizers above the requirement of agricultural crops. Thus, the use of phosphate fertilizers that contain aggregate technology can be an alternative to reduce P sorption in the soil and increase P availability when compared to conventional phosphate fertilizers. This thesis objective was: i) to evaluate the interaction of coffee straw (CSB), poultry litter (PLB) and eucalyptus bark (EBB) biochars with the P ion and this interaction on P availability effects in the soil; ii) to produce organophosphate fertilizers based on biochars (CSB, PLB and EBB) with greater efficiency compared to conventional phosphate fertilizers. To this end, the thesis carried out laboratory, greenhouse and field conditions experiments, which presented throughout the search in four chapters. In Chapter 1, the aim of the study was to investigate the biochars effect (CSB, PLB and EBB), as well as the effect of ash removal from these biochars on phosphate sorption on soil with variable load. The results indicated that the incorporation of biochars increased the P availability. Could decrease the maximum phosphate adsorption capacity by the soil by up to 25% and reduce the P binding energy to the soil, causing a greater proportion of P sorbed, in order to be desorbed. In Chapter 2, the objective was to evaluate the P solubility and availability in the soil in contact with organophosphate fertilizers based on biochars and triple superphosphate (TSP) over time in the laboratory. The results showed that organophosphate fertilizers had lower P solubility in water. PLB-based fertilizers showed up to 50% lower water solubility than TSP. The coated preparation mode promoted lower initial P release; however, it presents a higher final release than the homogeneous mixture mode. A higher biochar proportion in the fertilizer reduces the water fertilizer solubility. The organophosphate fertilizers presented the lowest initial P release in the soil. However, they also presented the smallest P contents reduction in contact over time. In Chapter 3, the objective was to evaluate the organophosphate fertilizers produced from CSB, PLB and EBB efficiency in coating mode and homogeneous mixture using corn as a test plant in the greenhouse. On average organophosphate fertilizers showed 5.52% agronomic efficiency and 8.16% for P recovery rate higher than TSP. Fertilizers produced in coating mode provided higher P content in the plant and P recovery rate. Considering the higher agronomic efficiency, the 30% biochar/TSP ratio proved to be more efficient. In Chapter 4, the objective was to evaluate the efficiency of organophosphate fertilizers produced from CSB, PLB and EBB in coating mode and homogeneous mixture in corn cultivation under field conditions. Compared to TSP, organophosphate fertilizers showed greater agronomic efficiency (10.8%), P recovery (2.4%) and greater P availability in the soil after harvest (13.2 mg dm-3 ). Fertilizers produced from PLB stood out among the highest averages of agronomic efficiency and P recovery, in addition to having the highest concentration of P available in the soil after harvest. As for the preparation mode, the fertilizers produced in the coating mode promoted greater P availability in the soil. Considering the greater agronomic efficiency and P recovery, the 30% biochar/TSP ratio proved to be more efficient, in addition to promoting a greater P residual effect in the soil.